2021
DOI: 10.3390/nu13072379
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Fluctuation and Severe Internal Carotid Artery Siphon Stenosis in Type 2 Diabetes Patients

Abstract: The impact of glucose fluctuation on intracranial artery stenosis remains to be elucidated. This study aimed to investigate the association between glucose fluctuation and intracranial artery stenosis. This was a cross-sectional study of type 2 diabetes mellitus (T2DM) patients equipped with the FreeStyle Libre Pro continuous glucose monitoring system (Abbott Laboratories) between February 2019 and June 2020. Glucose fluctuation was evaluated according to the standard deviation (SD) of blood glucose, coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Pathophysiologically, glucose fluctuation, particularly the short-term glycemic fluctuation has been associated with the severity of systematic atherosclerosis, possibly via the inducing oxidative stress, inflammatory cytokines, and endothelial damage [ 27 , 28 ]. Consistently, a recent cross-sectional study showed that glucose fluctuation is significantly associated with severe siphon stenosis of internal carotid artery in T2DM patients, suggesting that glucose fluctuation might be a risk factor for intracranial artery stenosis and ischemic stroke [ 29 ]. An early study also showed that time-scale-dependent glycemic fluctuations might contribute to brain atrophy and cognitive outcomes in patients with T2DM, which may deteriorate the cognitive function after stroke [ 30 ].…”
Section: Discussionmentioning
confidence: 57%
“…Pathophysiologically, glucose fluctuation, particularly the short-term glycemic fluctuation has been associated with the severity of systematic atherosclerosis, possibly via the inducing oxidative stress, inflammatory cytokines, and endothelial damage [ 27 , 28 ]. Consistently, a recent cross-sectional study showed that glucose fluctuation is significantly associated with severe siphon stenosis of internal carotid artery in T2DM patients, suggesting that glucose fluctuation might be a risk factor for intracranial artery stenosis and ischemic stroke [ 29 ]. An early study also showed that time-scale-dependent glycemic fluctuations might contribute to brain atrophy and cognitive outcomes in patients with T2DM, which may deteriorate the cognitive function after stroke [ 30 ].…”
Section: Discussionmentioning
confidence: 57%
“…For example, increased glycemic fluctuation has been associated with vascular complications of diabetes and atherosclerosis of cerebral arteries, and cerebral ischemia has been identified as major risk factors for cognitive impairment in these patients [ 28 ]. A recent study showed that glucose fluctuation is significantly associated with severe internal carotid artery siphon stenosis in T2DM patients [ 29 ], a known cause of vascular dementia. In addition, increased glycemic fluctuation is related to the severity of oxidative stress, a major pathogenesis and therapeutic target for AD-related dementia [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, increased glycemic fluctuation has been associated with enhanced inflammatory response [44] and oxidative stress [45], two key factors that have been involved in the development of functional impairment in patients after AIS [46]. Moreover, a cross-sectional study showed that glucose fluctuation is significantly associated with severe internal carotid artery siphon stenosis, which may also be a marker of poor prognosis in patients with AIS [47]. Interestingly, a recent clinical trial showed that targeted intervention to reduce acute glycemic fluctuation was associated with improved nerve function for diabetic patients following AIS [48].…”
Section: Discussionmentioning
confidence: 99%